In triangle \( \triangle TUV \), we know that it is isosceles with \( \angle T \cong \angle V \) and \( m\angle U = 54^\circ \).
Since the sum of the angles in any triangle is always \( 180^\circ \), we can express this as:
\[ m\angle T + m\angle V + m\angle U = 180^\circ \]
Let \( m\angle T = m\angle V = x \). Then we can replace \( m\angle U \) with \( 54^\circ \):
\[ x + x + 54^\circ = 180^\circ \]
This simplifies to:
\[ 2x + 54^\circ = 180^\circ \]
Now, subtract \( 54^\circ \) from both sides:
\[ 2x = 180^\circ - 54^\circ \] \[ 2x = 126^\circ \]
Now, divide by 2:
\[ x = 63^\circ \]
So, \( m\angle T = 63^\circ \).
Therefore, the correct response is:
m∠T = 63°.